The article in oblique relative clauses [prep.+ (definitive art.) + que] in 18th century hispanoamerican texts El artículo en las relativas oblicuas [prep. + (art. definido) + que] en textos americanos del siglo XVIII = The article in oblique relative clauses [prep.+ (definitive art.) + que] in 18th century hispanoamerican texts - Martha GUZMÁN RIVERÓN (Cuadernos Dieciochistas)
The use of the article in sentences like la casa en (la) que vivo, among other variations, is today less frequently used in Hispanoamerica. Although we know that this structure, documented as early as the 13th century, became more wide-spread in the 18th century, little is known about its evolution at the time in American sources. I study the evolution of this phenomenon, basing myself exclusively on 18th century American texts. I also explore which factors are apparently related to this linguistic development and if the pace of its spread was determined by the preceding prepositions. Aiming at a panoramic view of the spread of the article in the period in question, I also trace the appearance of these relative clauses, with and without article, in the texts collected in the CORDE, and provide detailed analyses of texts from both halves of the century, in order to evaluate the factors that may have influenced this change. El uso del artículo en estructuras como la casa en (la) que vivo presenta hoy en día, entre otras variaciones, una frecuencia de uso menor en Hispanoamérica que en España. Aunque sabemos que este uso, documentado desde el siglo XIII, comienza realmente a extenderse justo en el XVIII, poco conocemos de su evolución en la época en fuentes americanas. En este trabajo, basándonos exclusivamente en textos americanos del XVIII, perseguimos investigar cómo evoluciona este fenómeno en documentación de esta procedencia. También intentaremos explorar qué factores están aparentemente en relación con este cambio e investigar si, en diferentes preposiciones, diverge el ritmo de difusión de su uso. Con vistas a obtener una idea general sobre la extensión del artículo en la época, rastrearemos las apariciones de dichas relativas —con y sin artículo— en los textos americanos recogidos en el CORDE. Para evaluar los factores que pueden incidir en él estudiaremos en detalle determinados textos de ambas mitades del siglo.